Brain parenchyma penetration by intrathecal ionic and nonionic contrast media. - Sage, M R; Wilcox, J; Evill, C A; Benness, G T (American Journal of Neuroradiology, 1982)
Metrizamide, a nonionic water-soluble contrast medium, has been shown to penetrate normal brain when injected intrathecally. Recently it was suggested that the complications following intrathecal metrizamide are directly related to the cerebral concentration reached. Metrizamide, both in experimental animals and clinically, is regarded as less neurotoxic than equivalent iodine concentrations of ionic contrast media. In this study the degree and depth of brain penetration of intrathecal metrizamide and methylglucamine iothalamate (Conray 280), using a similar iodine concentration (280 mg l/ml), was compared at 1 hr in adult greyhound dogs. The depth of penetration and concentration reached in the cortical gray matter was determined by coronal computed tomographic scanning of the brain after removal. No significant difference was found between the two contrast media, suggesting that the rate of diffusion across the cerebrospinal fluid-brain interface is similar and that the difference in neurotoxicity is not explained by a reduced concentration of contrast medium in the case of nonionic metrizamide, when compared with ionic methylglucamine iothalamate. Using Evans blue as a qualitative marker, no evidence of gross blood-brain disruption was demonstrated in the area of maximum penetration with either contrast medium.